Diseño e implementación de un plan de sucesión basado en competencias para el cargo de molinero en la planta de producción del molino de Cayambe de la empresa Moderna Alimentos SA., durante el año 2016 - Sango Quinga, Mónica Alexandra (2017)
This project involves the design and implementation of a succession plan for the position of a miller. This was identified as a critical charge for Moderna Alimentos by directly impact its core business and because within the labor market, there are no people ready to assume this position. It is essential to train staff from within the organization, and with a succession plan properly designed to be possible the identification of people with high potential in the medium and long term to occupy the position, providing the training necessary for them to assume it successfully. To determine the successor of this position is vital to obtain objective results of each of the candidates for which performance evaluations and assessments of potential was used. The first tool helps to identify the level adjustment the person in charge, comparing the actual profile vs. the ideal profile, through evaluating knowledge and skills which are visible aspects. The second tool is to investigate deeper aspects of people, those that are not evident because they are not intrinsic but are the engine that drives them. After contrasting the results of these two evaluations, the final result was to define the successor to the miller position.